The link between cognitive abilities and quality of life among patients with traumatic brain injury - Ivleva, Viktorija; Jurkuvėnas, Vytautas (Psichologija, 2018)
It is known that a traumatic brain injury causes different consequences, affecting not only a person’s physical health but also damaging one’s cognitive functions. The consequences of traumatic brain injury are negatively related to an individual’s quality of life. However, obtained research results regarding the health-related quality of life are often ambiguous and contradictory. Thus, it is unclear what impact do impaired cognitive functions have on the quality of life after a traumatic brain injury. The aim of the present study was to analize the link between cognitive functions and the quality of life among patients with traumatic brain injuries and healthy subjects. Two samples participated in this study – 46 patients with traumatic brain injuries and a control group of 60 healthy people. The age of the participants ranged from 20 to 81 years (M=44.60, SD=15.49). Of the participants, 51 were men (48.1%), and 55 – women (51.9%). The clinical group of participants consisted of the survivors of mild traumatic brain injuries. Based on the GCS (Glasgow Coma Scale), the traumas were evaluated within a range of 13–15 points. The present study was conducted in the Department of Physical Medicine, Rehabilitation and the Department of Neurology at the Republican Hospital of Vilnius University. A part of the sample was interviewed at the Department of Neurological Rehabilitation at the Kaunas Clinics of the Lithuanian University of Health Sciences. The cross-sectional study design was selected and the data were collected using a Hopkins Verbal Learning Test-Revised (HVLT-R), while a Trail Making Test was utilized for studying the attention, the speed of its transferring as well as the executive functions of the participants; the study also made use of the short version of the World Health Organization Quality of Life Questionnaire a (WHOQOL BREF). The study revealed that cognitive functions are not associated with the quality of life among both TBI survivors and healthy controls. While evaluating the quality of the lives of TBI survivors and healthy participants, it was revealed that the TBI survivors give lower scores for their physical health scale; however, there were no significant differences in any other fields of life quality. When examining the differences of the cognitive functions of the participants, a connection between age and education was noticed. These results indicate that the survivors of traumatic brain injuries have lower cognitive abilities than healthy ones. However, cognitive functions are only partially related to the quality of life.
Keywords: traumatic brain injury; neuropsychological assessment; quality of life; cognitive abilities